Individual Differences in Self-Talk Frequency: Social Isolation and Cognitive Disruption - Brinthaupt, Thomas M. (Frontiers in Psychology, 2019)
Despite the popularity of research on intrapersonal communication across many disciplines, there has been little attention devoted to the factors that might account for individual differences in talking to oneself. In this paper, I explore two possible explanations for who people might differ in the frequency of their self-talk. According to the “social isolation” hypothesis, spending more time alone or having socially-isolating experiences will be associated with increased self-talk. According to the “cognitive disruption” hypothesis, having self-related experiences that are cognitively disruptive will be associated with increased self-talk frequency. Several studies using the Self-Talk Scale (Brinthaupt, Hein, & Kramer, 2009) are pertinent to these hypotheses. Results indicate moderate support for the social isolation hypothesis and strong support for the cognitive disruption hypothesis. I conclude the paper with a wide range of implications for future research on individual differences in self-talk and other kinds of intrapersonal communication.